The Growing Importance of Clinical Trials in Pharmaceutical Development - Deepak Kumar Bhateja (Innovations in Pharmacy Planet, 2017)
In recent decades, the landscape of pharmaceutical development has undergone significant transformations, largely due to advancements in medical research, technology, and the growing need for effective treatments. At the heart of this transformation lies the clinical trial process — a critical phase in drug development that determines the safety, efficacy, and overall potential of new therapies. With increasing health challenges and an everexpanding global population, the role of clinical trials in the development of pharmaceuticals has never been more vital.